Revision of the genus Centrophorus (Squaliformes: Centrophoridae): Part 1—Redescription of Centrophorus granulosus (Bloch & Schneider), a senior synonym of C. acus Garman and C. niaukang Teng - White, William T.; Ebert, David A.; Naylor, Gavin J.p.; Ho, Hsuan-Ching; Clerkin, Paul; Veríssimo, Ana; Cotton, Charles F. (Zootaxa, 2013)
The genus Centrophorus is one of the most taxonomically complex and confusing elasmobranch groups. A revision of this group is currently underway and this first paper sets an important foundation in this process by redescribing the type species of the genus—Centrophorus granulosus. This taxon name has been previously applied to two different morphotypes: a large species >1.5 m TL and a smaller species 1 m TL. Centrophorus acus and C. niaukang are the most commonly used names applied to the larger morphotype. The original description of C. granulosus was based on a large specimen of 1.5 m TL, but subsequent redescriptions were based on either of the large or small morphotypes. Centrophorus granulosus is herein redescribed as a large species and a neotype is designated. Centrophorus acus and C. niaukang are found to be junior synonyms of C. granulosus. Centrophorus granulosus is distinguishable from its congeners by its large size, dermal denticle shape, colouration and a number of morphological and biological characteristics. Ontogenetic changes in morphology, dentition and denticle shape for this species are described in detail.